An ecocritical reading of selected works by post-independence Malaysian writers - Ali Termizi, Arbaayah; Mohd Said, Nur Aainaa Amira (PJMH Publishing, 2020)
This paper presents an ecocritical reading of works by selected post-independence Malaysian writers namely Shahnon Ahmad, Kamarul Zaman Ariff and Rehman Rashid. These writers use Malaysia or parts of it as the ecological landscape in their works which are No Harvest but a Thorn (1966), Long Road to Merdeka (2006) and A Malaysian Journey (2006). Despite the works’ varied settings, these three share the commonality in how nature is foregrounded and its relationship with human is amplified. Thus this paper aims to place these writings within one of the key movements of ecocritical thought i.e. material ecocriticism whereby both human and non-human co-exist and interconnected with each other via storied matter. The finding of this study thus broadens the scope of environmental consciousness in non-anthropocentric terms in writings which do not originally belong in a nature-writing genre as well as shares the humanistic values pertaining cohabitation of human and non-human.